Passive immunization with anti-Tau antibodies in two transgenic models: reduction of Tau pathology and delay of disease progression - Chai, Xiyun; Wu, Su; Murray, Tracey K; Kinley, Robert; Cella, Claire V; Sims, Helen; Buckner, Nicola; Hanmer, Jenna; Davies, Peter; O'Neill, Michael J; Hutton, Michael L; Citron, Martin (The Journal of biological chemistry, 2011)
The microtubule-associated protein Tau plays a critical role in the pathogenesis of Alzheimer disease and several related disorders (tauopathies). In the disease Tau aggregates and becomes hyperphosphorylated forming paired helical and straight filaments, which can further condense into higher order neurofibrillary tangles in neurons. The development of this pathology is consistently associated with progressive neuronal loss and cognitive decline. The identification of tractable therapeutic targets in this pathway has been challenging, and consequently very few clinical studies addressing Tau pathology are underway. Recent active immunization studies have raised the possibility of modulating Tau pathology by activating the immune system. Here we report for the first time on passive immunotherapy for Tau in two well established transgenic models of Tau pathogenesis. We show that peripheral administration of two antibodies against pathological Tau forms significantly reduces biochemical Tau pathology in the JNPL3 mouse model. We further demonstrate that peripheral administration of the same antibodies in the more rapidly progressive P301S tauopathy model not only reduces Tau pathology quantitated by biochemical assays and immunohistochemistry, but also significantly delays the onset of motor function decline and weight loss. This is accompanied by a reduction in neurospheroids, providing direct evidence of reduced neurodegeneration. Thus, passive immunotherapy is effective at preventing the buildup of intracellular Tau pathology, neurospheroids, and associated symptoms, although the exact mechanism remains uncertain. Tau immunotherapy should therefore be considered as a therapeutic approach for the treatment of Alzheimer disease and other tauopathies.